2021
DOI: 10.3389/fonc.2021.670214
|View full text |Cite
|
Sign up to set email alerts
|

Minimally-Invasive Versus Abdominal Hysterectomy for Endometrial Carcinoma With Glandular or Stromal Invasion of Cervix

Abstract: The purpose of the study was to evaluate the feasibility of laparoscopic approach versus laparotomy in endometrial cancer that extends to the cervix in the form of glandular extension and/or stromal invasion. A retrospective, single-center cohort study was conducted using data between 1995 and 2017 at an urban tertiary academic medical center. We identified patients who were diagnosed with endometrial cancer whose tumor involved the uterine cervix on final pathology. Operative and oncologic outcomes were compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…Minimally invasive surgery (MIS) is performed globally, and the LAP2 trial showed the safety and feasibility of laparoscopic surgery in staging operations for endometrial cancer [ 3 ]. Compared with traditional laparotomy, laparoscopic surgery is preferable owing to its shorter operation time, shorter hospital stay, and less intraoperative blood loss; thus, it is now considered the standard treatment for endometrial cancer [ 4 , 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Minimally invasive surgery (MIS) is performed globally, and the LAP2 trial showed the safety and feasibility of laparoscopic surgery in staging operations for endometrial cancer [ 3 ]. Compared with traditional laparotomy, laparoscopic surgery is preferable owing to its shorter operation time, shorter hospital stay, and less intraoperative blood loss; thus, it is now considered the standard treatment for endometrial cancer [ 4 , 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%